2013
DOI: 10.1002/asi.22806
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of research citation impact in nanoscience and nanotechnology

Abstract: This study investigates a range of metrics available when a nanoscience and nanotechnology article is published to see which metrics correlate more with the number of citations to the article. It also introduces the degree of internationality of journals and references as new metrics for this purpose. The journal impact factor; the impact of references; the internationality of authors, journals, and references; and the number of authors, institutions, and references were all calculated for papers published in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
1
9

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 140 publications
(96 citation statements)
references
References 57 publications
(114 reference statements)
7
78
1
9
Order By: Relevance
“…The results are consistent with previous studies (Didegah & Thelwall, 2013;Bornmann, Schier, Marx, & Daniel, 2012;Haslam et al, 2008;Kostoff, 2007;Boyack & Klavans, 2005;Peters & van Raan, 1994).…”
Section: The Impact and The Number Of Referencessupporting
confidence: 83%
See 3 more Smart Citations
“…The results are consistent with previous studies (Didegah & Thelwall, 2013;Bornmann, Schier, Marx, & Daniel, 2012;Haslam et al, 2008;Kostoff, 2007;Boyack & Klavans, 2005;Peters & van Raan, 1994).…”
Section: The Impact and The Number Of Referencessupporting
confidence: 83%
“…The same result has also been found in the previous literature (Didegah & Thelwall, 2013;Boyack & Klavans, 2005;Callaham, Wears, & Weber, 2002). Based on the results, if the JIF increases by one unit, the mean citation counts of articles in Chemistry, Social Sciences and Biology & Biochemistry increase by 31.9%, 27.8%, and 15.6%, respectively.…”
Section: Journal Impactsupporting
confidence: 75%
See 2 more Smart Citations
“…Franceschet & Costantini (2010), in an investigation of 970 Italian economics and statistics articles, found that the citation level increased as the number of authors increased from 1 to 2 and from 2 to 3 or more. Didegah and Thelwall (2013), in a study of nanotechnology articles, found that the number of authors was not a significant determinant of citations once other factors, such as various types of internationality, were taken into account. Levitt (2015), in an investigation of nineteen social science disciplines for the years 1995, 1998, 2001, 2004 and 2007, found that, although the mean citation counts rose as the number of authors increased from 1 to 4, by far the largest rise occurred when the number of authors increased from 1 to 2.…”
Section: : Citation Productivity and Group Sizementioning
confidence: 99%